2020
DOI: 10.1093/jac/dkaa067
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of ceftriaxone administered as continuous or intermittent infusion in critically ill patients

Abstract: Objectives To describe the population pharmacokinetics and protein-binding characteristics of unbound ceftriaxone administered as continuous or intermittent infusion. Additionally, to determine the optimal dosing regimen in critically ill patients. Methods A pharmacokinetic study was performed in the ICU of a tertiary teaching hospital. Patients were treated with ceftriaxone as continuous or intermittent infusion. A populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
6
23
0
Order By: Relevance
“…In accordance with previous PK studies in septic [ 9 ], general ICU [ 10 , 11 , 12 ] or non-ICU [ 18 ] patients, PK/PD target attainment was suboptimal for ceftriaxone 2 g q24h in patients with severe CAP. Interestingly, despite the relatively high age in our study population, renal function was still well preserved.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In accordance with previous PK studies in septic [ 9 ], general ICU [ 10 , 11 , 12 ] or non-ICU [ 18 ] patients, PK/PD target attainment was suboptimal for ceftriaxone 2 g q24h in patients with severe CAP. Interestingly, despite the relatively high age in our study population, renal function was still well preserved.…”
Section: Discussionsupporting
confidence: 86%
“…Next to meropenem and piperacillin, ceftriaxone is one of the most frequently monitored β-lactams in the ICU [ 8 ]. Studies have shown suboptimal PK/PD target attainment in septic [ 9 ] or general ICU [ 10 , 11 , 12 ] patients treated with ceftriaxone. Nevertheless, routine TDM for ceftriaxone has still not found its way into clinical practice [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thought that the chosen high breakpoints for target attainment were necessary due to the high number of immunocompromised patients who underwent lung or liver transplantation and had special pathogens with higher MICs than other patients [31,32]. The number of subtherapeutic levels was comparable to those reported in the literature for meropenem [17,33,34], piperacillin [7,35,36], and other beta-lactam antibiotics like cefepime [37] or ceftriaxone [38]. Furthermore, the existing correlation between renal function and beta-lactam blood concentration has also been described in different studies [21,22].…”
Section: Discussionmentioning
confidence: 77%
“… Exclusion—RRT, life expectancy < 12 h. Model covariates—adjusted body weight, plasma albumin concentration, creatinine clearance (Cockcroft-Gault), method of administration (continuous infusion or intermittent bolus). Garot D et al [ 126 ] Leegwater E et al [ 127 ] [ 126 , 127 ] Ciprofloxacin Adult ICU. N = 102 patients (588 plasma samples).…”
Section: Table A1mentioning
confidence: 99%